Flooding effects on population and growth characteristics of Bolboschoenus planiculmis in Momoge wetland, northeast China. (April 2022) - Zhang, Mingye; Zhang, Dongjie; Qi, Qing; Tong, Shouzheng; Wang, Xuehong; An, Yu; Lu, Xianguo
Highlights: Flooding events have significant effects on growth of Bolboschoenus planiculmis . B. planiculmis adopted growth strategies to cope with different flooding stress. Alternating wet-flooding condition is more beneficial to the growth of B. planiculmis. Abstract: Due to the interactive influences of climate change and human activities, flooding events are becoming an increasingly more serious abiotic stress in wetland ecosystems. Bolboschoenus planiculmis is a critical target plant species for the restoration of degraded wetland in the Momoge National Nature Reserve (MNNR), Northeast China. To investigate B. planiculmis growth response under different flooding conditions, we conducted comparative field studies of its population traits and ecological characteristics under alternate wetting to flooding (AF) and continuous flooding (CF) conditions. Under AF conditions, the B. planiculmis population significantly increased, its cover differed significantly (except June) compared to CF conditions, and flood stress significantly promoted its height. Flood events caused seasonal changes in morphological characteristics, especially stem and leaf length which increased in the growth period, and leaf width and area that significantly differed in June. B. planiculmis tuber biomass under CF condition was significantly higher than AF condition in May. B. planiculmis biomass was greater in AF, compared to CF conditions in the mid-late growth period, and its below-aboveground biomass ratio initially decreased before increasing, which indicated that the growth strategy was a trade-off between matter production and allocation during flooding. Flooding conditions had a significant effect on population traits and ecological characteristics, and AF conditions more strongly promoted B. planiculmis population development. Appropriate seasonal regulated floodwater management during the growth stage will assist B. planiculmis growth. Our findings provide invaluable supporting information for B. planiculmis MNNR wetlands restoration and management.